Playing unpredictably: measuring the entropy of ball trajectories in international women's basketball. (2nd January 2018) - Hobbs, Wade; Morgan, Stuart; Gorman, Adam D.; Mooney, Mitchell; Freeston, Jonathan
Abstract: It is generally accepted that playing unpredictable basketball is advantageous, however this strategic assumption has not been adequately tested. The aim of this study was to describe unpredictability of in-play ball movement trajectories during a selection of women's international basketball games to determine the association, if any, between unpredictability and success in basketball. Ball movements were tracked for 60 international women's basketball games over a two-year period. Ball movements were broken into five-second play segments and the spatial distribution of the ball was tracked across the court. Shannon's entropy was then used to estimate the relative variability in ball movements. While no differences in entropy were observed between teams, the overall analysis revealed that entropy during large-deficit games (score differential of 10 points or more) was greater than that for small-deficit games and large-deficit wins showed greater entropy than large-deficit losses. Additionally, the entropy in the frontcourt (the scoring end for a given team) was significantly greater for wins compared to losses. This suggests that higher entropy may be associated with success in basketball, but more specifically, entropy in the frontcourt is potentially where it matters most.